KARBON AKTIF TERMODIFIKASI NANOSILVER - Rengga, Wara Dyah Pita; Hand, Prima Astuti (Sainteknol : Jurnal Sains dan Teknologi, 2016)
Carbon was prepared from dried waste bamboo (Dendrocalamus asper) using chemical activation with KOH. The carbon was prepared with the activating agent in a mass ratio of KOH and dried bamboo (3:1) at 800oC. Using impregnation technique, the bamboo-based activated carbon has developed with modified Ag nanoparticle (Ag-AC) to capture formaldehyde. The Ag-AC has characteristics of moderate surface area of 685 m/g and average pore size of 2.7 nm. The adsorption equilibriums and kinetics of formaldehyde on Ag-AC measured. The influences of initial formaldehyde on adsorption performance have measured in a batch system. The equilibrium data were evaluated by isotherm models of Langmuir, Freundlich, and Temkin. The Langmuir model well describes the adsorptive removal of formaldehyde on Ag-AC in this study. Pseudo-first-order and pseudo-second-order kinetic equations were applied to test the experimental data. The pseudo-second-order exhibited the best fit for kinetic study.